2018
DOI: 10.1073/pnas.1717617115
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and ecological function of the root microbiome across angiosperm plant species

Abstract: Across plants and animals, host-associated microbial communities play fundamental roles in host nutrition, development, and immunity. The factors that shape host-microbiome interactions are poorly understood, yet essential for understanding the evolution and ecology of these symbioses. Plant roots assemble two distinct microbial compartments from surrounding soil: the rhizosphere (microbes surrounding roots) and the endosphere (microbes within roots). Root-associated microbes were key for the evolution of land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
642
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 831 publications
(713 citation statements)
references
References 67 publications
63
642
5
3
Order By: Relevance
“…Our findings support recent studies showing that microbial communities are sensitive to phylogenetic distance among host plants (Bouffaud et al 2014, Naylor et al 2017) and plant species exhibit phylogenetic signal in the structure of soil microbial communities (Fitzpatrick et al 2018), at least with regard to organisms inhabiting the root ecto-and endosphere. Our findings support recent studies showing that microbial communities are sensitive to phylogenetic distance among host plants (Bouffaud et al 2014, Naylor et al 2017) and plant species exhibit phylogenetic signal in the structure of soil microbial communities (Fitzpatrick et al 2018), at least with regard to organisms inhabiting the root ecto-and endosphere.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support recent studies showing that microbial communities are sensitive to phylogenetic distance among host plants (Bouffaud et al 2014, Naylor et al 2017) and plant species exhibit phylogenetic signal in the structure of soil microbial communities (Fitzpatrick et al 2018), at least with regard to organisms inhabiting the root ecto-and endosphere. Our findings support recent studies showing that microbial communities are sensitive to phylogenetic distance among host plants (Bouffaud et al 2014, Naylor et al 2017) and plant species exhibit phylogenetic signal in the structure of soil microbial communities (Fitzpatrick et al 2018), at least with regard to organisms inhabiting the root ecto-and endosphere.…”
Section: Discussionsupporting
confidence: 91%
“…Plant functional traits, such as SRL, root N concentration and aboveground biomass explained microbial community composition in various studies (Legay et al 2014;Legay et al 2016;PerezJaramillo et al 2017;Fitzpatrick et al 2018), but not in Leff et al (2017) and Leff et al (2018).…”
Section: Plant Functional-traits Explain Rhizosphere Microbiomesmentioning
confidence: 95%
“…Other studies, likewise, found that variation in microbial community composition can be explained by plant functional traits (Cantarel et al 2015;Perez-Jaramillo et al 2017;Fitzpatrick et al 2018). However, it remains to be tested how results obtained in individual plants grown in controlled conditions translate into effects in plant communities, as results on plant community level are contradictory.…”
Section: Rhizosphere Microbial Community Assemblymentioning
confidence: 99%
See 2 more Smart Citations